Neutrophils amplify the formation of DNA adducts by benzo[a]pyrene in lung target cells. - Borm, P J (1997)
Inflammatory cells and their reactive oxygen metabolites can cause mutagenic effects in lung cells. The purpose of this study was to investigate the ability of activated neutrophils to modulate DNA binding of benzo[a]pyrene (B[a]P), a known carcinogen, in lung target cells. Equivalent numbers of rat lung epithelial cells (RLE-6TN cell line) and freshly isolated human blood neutrophils (PMN) were coincubated in vitro for 2 hr after addition of benzo[a]pyrene (0.5 microM) or two of its trans-diol metabolites, with or without stimulation with phorbol myristate acetate (PMA). DNA adducts of B[a]P-metabolites were determined in target cells using 32P-postlabeling; oxidative DNA damage (7-hydro-8-oxo-2'-deoxyguanosine [8-oxodG]) was evaluated by high performance liquid chromatography with electrochemical detection. Increased DNA adducts were observed in lung cells coincubated with polymorphonuclear leukocytes (PMN). Activation of PMN with PMA, or addition of more activated PMN in relation to the number of lung cells, further increased the number of adducts, the latter in a dose-response manner. Incubation with B[a]P-4,5-diol did not result in any adduct formation, while B[a]P-7,8-diol led to a significant number of adducts. Moreover, PMA-activated PMN strongly enhanced adduct formation by B[a]P-7,8-diol, but not 8-oxodG, in lung cells. The addition of antioxidants to the coincubations significantly reduced the number of adducts. Results suggest that an inflammatory response in the lung may increase the biologically effective dose of polycyclic aromatic hydrocarbons (PAHs), and may be relevant to data interpretation and risk assessment of PAH-containing particulates.